STATUS ANALYSIS OPEN DEFECATION FREE (ODF) OF LAND AVAILABILITY AND ECONOMIC STATUS IN SAGULUNG DISTRICT, BATAM CITY: Analysis Open Defecation Free (ODF) Of Land Availability and Economic Status in Sagulung District, Batam City - Ahmadi, Ahmadi; Saputra, Roni (Fakultas Ilmu Kesehatan, Universitas Ibnu Sina, 2021)
The implementation of the First Pillar STBM Program in Sagulung District, Batam City, which began in 2018 as a whole, has not been carried out optimally with results that are still far from the SDGs 2030 target and the Circular (SE) of the Governor of Riau Islands No. 0168/106 / SET regarding the 2019 universal access target for sanitation. The purpose of this study was to analyze the Open Defecation Free (ODF) status on land availability and economic level status in Sagulung District, Batam City. This research is an observational study with a quantitative method with a cross-sectional design. The research was conducted in Sagulung District from April to May 2020, the research sample was determined by random sampling technique, namely as many as 90 samples. The results showed that of the 6 Village in Sagulung District, there were 3 Village that had been ODF verified and 3 Village had not been ODF verified, with the status of having land to build latrines were 25 samples (27.8%) and did not have land to build latrines and septic tanks were as many as 65 samples (72.2%) with a p-vlaue is = 0.585 while the economic level with good status was 58 samples (64.4%) and bad was 32 samples (35.6%) p-value = 0.274. From the results of this study it can be concluded that there is no relationship between land availability and economic status for ODF status in Sagulung District, Batam City. It is hoped that the Batam City Health Office can advocate for the local government to build more communal latrines in Sagulung District and turn coastal areas into tourist areas so that people are ashamed of open defecation and the need to mobilize figures to implement policies or written regulations agreed upon by the local community to encourage so that people do not defecate anywhere anymore.